Serum chemerin levels in women with polycystic ovary syndrome - (:unkn) unknown (WALTER DE GRUYTER GMBH, 2015)
Objective: The aim of this study is to investigate the association of serum chemerin levels with metabolic parameters of women with polycystic ovary syndrome. Chemerin is an adipocytokine associated with adiposity, insulin resistance and metabolic syndrome, all of which are frequently observed in polycystic ovary syndrome. Methods: This is a prospective case-control study. We compared the metabolic, biochemical and anthropometric parameters of 35 women with polycystic ovary syndrome and 30 body mass index and age matched controls. Results: Chemerin levels of women with polycystic ovary syndrome were similar to that of the control group. Chemerin levels correlated positively with DHEAS (r=0.427, p=0.011) and LH (r=0.407, p=0.015) levels in women with polycystic ovary syndrome. There was a negative correlation between chemerin and lipoprotein-a levels in normal weight women with polycystic ovary syndrome (r=-0.426, p=0.043) and there was a negative correlation between chemerin and triglyceride levels in overweight women with polycystic ovary syndrome (r=-0.669, p=0.024). In obese control group chemerin correlated positively with C-reactive protein levels (r=0.738, p=0.037). Conclusion: In this study we could not detect a definitive role of chemerin in the pathophysiology of polycystic ovary syndrome, but its probable role in the development of the syndrome should be investigated with more detailed studies in the future.
Keywords: Chemerin; Polycystic Ovary Syndrome; CRP; body mass index; METABOLIC SYNDROME; INSULIN-RESISTANCE; ADIPOSE-TISSUE; INFLAMMATION; OBESE; STEROIDOGENESIS; ASSOCIATION; MARKERS; RISK